TRUE SALE ACCOUNTING ON SECURITIZATION IN INDONESIA - Heliantono Heliantono (International Journal of Contemporary Accounting, 2019)
Asset securitization is one of the financing solutions. One application for the use of asset securitization is in the residential mortgage sector. Securitization in Indonesia so far has been discussed in terms of financial management and legal aspects. This article discusses about securitization in Indonesia in term of accounting perspective. The accounting aspects of securitization transactions are based on the occurrence or non-occurrence of the derecognition of the financial assets securitized (true sale in accounting).  Asset securitization in Indonesia is carried out with the issuance of Asset-Backed Securities Collective Investment Contracts (KIK EBA) and Asset-Backed Securities in the form of Participation Certificate (EBA SP) with a total of 15 EBAs which are still traded at present. Eighty percent are residential mortgages backed securities (RMBS), the rest are non-RMBS.  The accounting treatment of securitization transactions conducted by the originator and in the event of an accounting true sale and non-true sale are discussed, also the securitization accounting treatment for originator, Special Purpose Vehicle (SPV), and investors. Broader socialization is needed so securitization can be applied in various economic activities to benefit national development in Indonesia